Animated Stories In The Teaching Of Writing - Rahmawati, Henny; Kurniasih, Kurniasih (Universitas Islam Malang, 2017)
This study is aimed at investigating the benefits of animated stories in the teaching of writing as suggested by Cahyono, Hidayati, & Zen (2014). This study is, say, a literature review study in which the researcher reviews the material related to the issue and observes the students as well to strengthen the validity of this study. The data obtained from both literature and observation are then analyzed qualitatively showing that the animated stories are not only interesting for the students in writing class but also enable them to learn based on their learning style